A retrospective review of Achromobacter species and antibiotic treatments in patients with primary ciliary dyskinesia. (20th November 2021) - Holgersen, Mathias G; Marthin, June K; Johansen, Helle K; Nielsen, Kim G
Objectives: Primary ciliary dyskinesia (PCD) is a rare congenital disease with defective mucociliary clearance causing frequent and often persistent pulmonary infections. Achromobacter species are opportunistic pathogens renowned for the difficulty of effective treatments and deteriorating effects on lung function. We aimed to describe the occurrence, treatment, and rate of successful eradication of Achromobacter species in patients with PCD.Methods: We retrospectively reviewed 18 years of historical microbiological samples and 10 years of electronic health records for PCD patients in Denmark.Results: We included 136 patients. Twenty-six patients had isolates of Achromobacter species. On average, 5% of the cohort had at least one annual isolate. Infections became persistent in 38% with a median length of 6.6 years leading to a significant number of antibiotic treatments. Resistance toward tobramycin and ciprofloxacin was prevalent. Overall, successful eradication was achieved in 62% of patients. We found the course of lung function significantly worse during persistent Achromobacter species infection than during the two preceding years, but not different to the course in unaffected age-matched controls.Conclusion The prevalence of Achromobacter species in patients with PCD is in line with what has been reported in cystic fibrosis and can occur transiently, intermittently, or develop into a serious persistent lung infection associated with long-term antibiotic treatment.